EFFICIENT MECHANISM FOR SECURING SOFTWARE DEFINED NETWORK AGAINST ARP SPOOFING ATTACK - Y. I. KHALID, HARMAN; M. ISMAEL, PARISHAN; BAHEEJ AL-KHALIL, AHMAD (Journal of Duhok University, 2019)
Software Defined Network SDN is a new emerging paradigm of networking which decouples the data plane and the control plane. It is expected to be a solution to overcome the limitations of traditional networks. Conventional networks had several security problems, some of them disappeared by SDN and some others still exist such as Address Resolution Protocol ARP spoofing. This paper discusses the attacks of ARP spoofing and presents a deep study on the existing solutions either in traditional or SDN environments. A light, reliable, fast and effective mechanism has been proposed to prevent ARP spoofing, without any additional software or hardware by utilising SDN capabilities. In this work, the SDN controller has been extended by a module which checks every ARP packet in network to detect possible spoofed packets and stop them. Experiments were conducted on the simulated environment using Mininet to check the functionality of the proposed mechanism. The simulation results showed that the proposed mechanism is robust against ARP spoofing attack.